Differential Protection of Transmission Transformer for Large-Scale Doubly-Fed Wind Farms Based on Detrended Analysis - Yanchun XU; Zhongyao FAN; Sihan SUN; Lu MI (Zhongguo dianli)
Since the fault current output from the doubly-fed wind farm has frequency deviation characteristics and contains large harmonic components, when an internal fault occurs in the transmission transformer for the doubly-fed wind farm, the ratio of the second harmonic to the fundamental wave in the differential current of the transformer increases, which makes the differential protection of the transformer face the risk of delay action. Moreover, when the system fails, a large number of non-periodic components in the fault current output from the doubly-fed wind farm will make the current transformer in the transmission transformer more prone to saturation, resulting in reduced reliability of the differential protection of traditional transformers. This paper proposes a differential protection scheme for the transmission transformer for large-scale wind farms based on detrended analysis. Firstly, the sampling current is processed by detrended analysis through the sliding data window to obtain the detrended residual function, and then the slope characteristics of the current waveform are utilized to complete the effective distinction between the magnetizing inrush current and the fault differential current (including the current transformer saturation state) of the transformer. The proposed protection scheme is validated to be applicable under different operating conditions by building a transmission system for the doubly-fed wind farm in PSCAD.